2010
DOI: 10.1016/s1470-2045(10)70145-5
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life after total laparoscopic hysterectomy versus total abdominal hysterectomy for stage I endometrial cancer (LACE): a randomised trial

Abstract: Cancer Council Queensland, Cancer Council New South Wales, Cancer Council Victoria, Cancer Council Western Australia; NHMRC project grant 456110; Cancer Australia project grant 631523; The Women and Infants Research Foundation, Western Australia; Royal Brisbane and Women's Hospital Foundation; Wesley Research Institute; Gallipoli Research Foundation; Gynetech; TYCO Healthcare, Australia; Johnson and Johnson Medical, Australia; Hunter New England Centre for Gynaecological Cancer; Genesis Oncology Trust; and Sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
211
1
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 307 publications
(234 citation statements)
references
References 31 publications
17
211
1
5
Order By: Relevance
“…Its study design, data on early surgical recovery and postoperative QoL as well as data on the surgical safety of TLH were reported previously (7,10). In brief, patients were randomized to either TLH or TAH using stratified permuted blocks through a web-based system with concealment of the next allocated treatment to study staff.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Its study design, data on early surgical recovery and postoperative QoL as well as data on the surgical safety of TLH were reported previously (7,10). In brief, patients were randomized to either TLH or TAH using stratified permuted blocks through a web-based system with concealment of the next allocated treatment to study staff.…”
Section: Methodsmentioning
confidence: 99%
“…Results from our randomized controlled trial comparing TAH with total laparoscopic hysterectomy (TLH) (the LACE trial) found that patients undergoing TLH reported significantly better postsurgical improvement in Quality of Life (QoL) compared to TAH (7). This improvement in QoL continued to favour a laparoscopic approach for up to 6 months post-surgery.…”
Section: Introductionmentioning
confidence: 99%
“…The primary endpoints were the major complication rate and mortality rate, while the second end-points were total complication rate, postoperative complication rate and intra-operative complication rate. The major complications included injuries of bowel, bladder, ureter, vessel, nerves; thromboembolic events such as DVT (Deep Venous Thrombosis) or pulmonary embolism; haematoma requiring surgical intervention; hemorrhage requiring transfusion and/or surgical intervention; wound dehiscence requiring surgical intervention or re-admission; wound infections including vaginal vault abscess, requiring surgical intervention and/ or prolonged hospital stay and/or readmission and/or treatment; other major complications (Janda et al, 2010;Mourits et al, 2010).…”
Section: Data Extraction and Main Endpointsmentioning
confidence: 99%
“…Six studies were further excluded including one study for no available data (Nicklin et al, 2011) and 5 overlapping studies (Tozzi et al, 2005;Zullo et al, 2005;Bijen et al, 2009;. Finally, nine randomized controlled trials with a total of 1263 patients were included into this meta-analysis (Fram, 2002;Tozzi et al, 2005;Zorlu et al, 2005;Chen and Huang, 2007;Wang, 2008;Malzoni et al, 2009;Zullo et al, 2009;Janda et al, 2010;Mourits et al, 2010). The sample size in each trial was relatively small, ranging from 52 to 332 participants.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation